Interaction of the gas vesicle proteins GvpA, GvpC, GvpN, and GvpO of Halobacterium salinarum - Jost, Alisa; Pfeifer, Felicitas (Frontiers in Microbiology, 2022)
The interactions of the four gas vesicle proteins GvpA, C, N, and O were investigated by split-GFP and pulldown assays. GvpA forms the ribs of the gas vesicle shell, whereas GvpC is attached to the exterior surface and stabilizes the gas vesicle structure. The AAA-ATPase GvpN as well as GvpO is found in much lower amounts. GvpN and GvpO formed homodimers and also the GvpN/GvpO heterodimer; both interacted with the C-terminal domain of GvpC when tested by split-GFP. When analyzed by pulldown assays, GvpN and GvpO also selected GvpA. The N-and C-terminal fragments of GvpC dimerized as Cterm/Cterm and Cterm/Nterm, but not as Nterm/Nterm. These interactions at both termini might lead to a network of GvpC molecules at the gas vesicle surface. However, a GvpA/GvpC interaction was not detectable, suggesting that the contact of both proteins is either mediated by another Gvp, or requires different structures that might form when GvpA is aggregated in the gas vesicle shell. Interactions of GvpA, C, N, and O were also studied with the accessory proteins GvpF through GvpM by split-GFP. GvpN bound GvpL only, whereas GvpO interacted with GvpF, I, and L, and the C-terminal domain of GvpC contacted GvpF, H, I, and L. GvpA/GvpA interactions were difficult to detect by split-GFP, but GvpA selected except for GvpI, K, and L all other accessory Gvp in pulldown assays. We will discuss the implications of these findings on gas-vesicle assembly.